EU & the South Caribbean : Guyana, Suriname, Trinidad & Tobago, Aruba, Netherlands Antilles, Cariforum (Delegation of the European Commission to Guyana, Suriname, Trinidad & Tobago, Aruba and the Netherlands Antilles GeorgetownGY, 2003)
Provides information on the European Union and its partnership with the Southern Caribbean.
Keywords: EUROPEAN UNION